Jigsaw for Enhanced Gynecology Education of Undergraduate Students - Sonal Prasad; Prachi Renjhen; Ravi P Jha (Journal of Medical Academics)
Aim: With increasing MBBS batch sizes, traditional small-group teaching methods may not effectively promote knowledge gain and student satisfaction. This study aimed to evaluate the effectiveness of the jigsaw method compared to conventional small-group discussion (SGD) in teaching contraception to undergraduate medical students. Materials and methods: This 1-year study involved 150 phase 3 part II obstetrics and gynecology students, divided into two groups of 75. Group I was taught using the jigsaw method, while group II received conventional SGD. Pretests, posttests, and a retention test after 15 days were conducted to assess learning outcomes and knowledge retention. Students also rated their satisfaction, communication, and teamwork skills using a Likert Scale. Data were analyzed using the Statistical Package for the Social Sciences (SPSS). Results: The jigsaw group showed significantly higher posttest scores (72.8 ± 5.6%) compared to the SGD group (66.0 ± 6.3%) (p < 0.05). Retention scores were also higher for the jigsaw group (71.2 ± 6.1%) vs SGD (57.6 ± 7.0%). Students in the jigsaw group reported improved communication (92%) and teamwork skills (96%), along with higher overall satisfaction (84% rating ≥4 on the Likert Scale). Conclusion: The jigsaw method proved to be more effective than SGD in enhancing immediate learning, long-term retention, communication, and teamwork skills. Clinical significance: The jigsaw method offers a valuable approach to teaching complex topics such as contraception, fostering a collaborative learning environment, and improving critical soft skills, which are essential in medical education and practice.